TINJAUAN TERHADAP PEMBUATAN PERATURAN DESA DI DESA BHUANA JAYA KECAMATAN TENGGARONG SEBERANG KABUPATEN KUTAI KARTANEGARA - Hariyanto, Ismail (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACTThe village of Bhuana Jaya from 1983 to 2017 does not yet have definite rules regarding vilage information management guidelines, so the village goverment seeks to establish village regulation number 9 of 2017 concerning village information management guidlines (PPID) within the village goverment. In this study ″ Tinjauan Terhadap Pembuatan Perauran Desa Di Desa Bhuana Jaya Kecamatan Tenggarong Seberang Kabupaten Kutai Kartanegara .‶ with the formulation of the problem, namely how the stages in the formation of village regulation of the Minister of internal Affair number 111 of 2014 concerning technical guidelines in village regulations concerning village regulation number 9 of 2017 concerning village information management guidlines (PPID) in the environment of the village. The purpose of this study was to determine the stages of formation of village regulations and the application of Minister of Home Affair Regulation Number 111 of 2014 concerning village technical guidkines regarding village regulation Number 9 of 2017 concerning village information Management Guidlines (PPID) in the Village of Bhuana Jaya.The methode used is a normative empirical juridical research method, the data sources used are primary and secondary data, and village regulation data, whitch will be analized in this study through field research and literature.Based on the results of the research, that is in the stages of the process of establishing village regulations and the aplication of the number of ministerial regulations Number 111 of 2014 concerning technical guidlines in the village regarding village regulation number 9 of 2017 concerning village information Management Guidlines (PPID) in the Village of Bhuana Jaya with applicable laws and regulations.